2015
DOI: 10.1111/bju.12680
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the physical impact of complex surgical tasks on surgeon errors and discomfort: a comparison between robot‐assisted, laparoscopic and open approaches

Abstract: ObjectivesTo evaluate, in a simulated suturing task, individual surgeons' performance using three surgical approaches: open, laparoscopic and robot-assisted. Subjects and MethodsSix urological surgeons made an in vitro simulated vesico-urethral anastomosis. All surgeons performed the simulated suturing task using all three surgical approaches (open, laparoscopic and robot-assisted). The time taken to perform each task was recorded. Participants were evaluated for perceived discomfort using the self-reporting B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 27 publications
(11 reference statements)
0
24
1
Order By: Relevance
“…Previous studies have suggested that surgeons experience more musculoskeletal discomfort during minimally invasive surgery [2, 5, 13, 40]. However, we did not observe a higher number of musculoskeletal complaints among surgeons who perform more endoscopic surgeries compared with surgeons who perform more open surgeries.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have suggested that surgeons experience more musculoskeletal discomfort during minimally invasive surgery [2, 5, 13, 40]. However, we did not observe a higher number of musculoskeletal complaints among surgeons who perform more endoscopic surgeries compared with surgeons who perform more open surgeries.…”
Section: Discussioncontrasting
confidence: 88%
“…Respondents in both groups seemed to suffer of complaints (now or in the past). This discrepancy could, for example, be due to the fact that other studies categorize surgeons as solely laparoscopic surgeons when they are regularly involved in laparoscopic surgeries [2] or because of the variance in prior surgical experience [40]. This could lead to a higher number of surgeons categorized as ‘laparoscopic’, with musculoskeletal complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The more comfortable operating system may cause less fatigue to the surgeon as compared to laparoscopic methods, thereby leading to fewer errors. This was shown by Elhage et al (36) where time taken to perform a suturing task was not only shorter compared to laparoscopic and open, but there were also fewer errors made when compared to the laparoscopic method. The major limitation of this study is the possibility of bias.…”
Section: Discussionmentioning
confidence: 74%
“…The severity of problems reported by MIS surgeons varies, with most surgeons reporting neuromusculoskeletal symptoms during the MIS procedures [8] and others identifying symptoms that persist beyond the operative time [6,14] and extend beyond the work day [12]. Neuromusculoskeletal fatigue, impairment, and injuries have been shown to adversely affect MIS performance, patient safety, and surgeon career longevity [15][16][17][18][19][20]. The impact of suboptimal health on the ability of surgeons to perform quality MIS procedures is a major concern in hospitals worldwide [9,[21][22][23], prompting calls by medical practitioners and human factors engineers to request modification of the "hostile" and "dangerous" environment encountered by MIS surgeons [9,10,24,25].…”
Section: Introductionmentioning
confidence: 99%